2011
DOI: 10.1021/jp2052008
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Circular-Type Nanowire Transistors Grown on Multilayer Graphene Film

Abstract: High-performance transistors using semiconducting nanowires are very promising devices for flexible or transparent electronic applications. However, nanowire-based transistors inevitably have placement and alignment issues, which make them troublesome for real-world applications and can be limiting factors in novel applications. Here we present a novel device structure that can be easily adapted for producing high-yield nanowire transistors. We fabricated fully transparent circular tin oxide (SnO2) nanowire tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Graphene, a novel material for electronic device applications, has a high electrical conductivity, thermal stability, and optical transparency that make it ideal as a nextgeneration electrode material. 1,2 The number of investigations employing graphene films as electrodes for a variety of devices has recently increased, 3,4 and while nanowires (NWs) grown directly on graphene without a catalyst have been reported, 5 detailed studies of the contact properties between graphene and NWs are still required. Generally, metals such as Al and Ti, which exhibit work function values (4.28 eV and 4.33 eV, respectively) similar to the ZnO (one representative NW material) electron affinity (4.2 eV), have often been chosen as the electrodes for ohmic contacts to n-type ZnO materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene, a novel material for electronic device applications, has a high electrical conductivity, thermal stability, and optical transparency that make it ideal as a nextgeneration electrode material. 1,2 The number of investigations employing graphene films as electrodes for a variety of devices has recently increased, 3,4 and while nanowires (NWs) grown directly on graphene without a catalyst have been reported, 5 detailed studies of the contact properties between graphene and NWs are still required. Generally, metals such as Al and Ti, which exhibit work function values (4.28 eV and 4.33 eV, respectively) similar to the ZnO (one representative NW material) electron affinity (4.2 eV), have often been chosen as the electrodes for ohmic contacts to n-type ZnO materials.…”
mentioning
confidence: 99%
“…The graphene thin film used in this study was fabricated with a Ni catalyst and transferred onto the substrate as in our previous studies. 5 Figure 1(b) shows a high-resolution transmission electron microscopy (HR-TEM) cross-sectional image of the fabricated multilayer graphene film (MGF) that consisted of approximately 20 graphene layers, with a total thickness of 6-6.5 nm and a sheet resistance and mobility of approximately 200 X/sq and 1200 cm 2 /VÁs, respectively. The MGF Raman spectrum (Figure 1(b) inset) measured by Raman microscopy showed that the graphene quality was remarkable; the 2D band has a sharp peak (at 2700 cm À1 ), the D band has a low peak (at 1350 cm À1 ), and the 2D/G band ratio is greater than 0.5 (the G band is at 1580 cm À1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation